Six new species of Coelotinae spiders from Nangunhe National Nature Reserve, Yunnan, China (Araneae: Agelenidae) - Kong, Jin-Xia; Li, Lao-Da; Yang, Zi-Zhong; Zhang, Zhi-Sheng (Zootaxa, 2025)
Four new Draconarius Ovtchinnikov, 1999 species and two new Sinocoelotes Zhao & Li, 2016 species from the Nangunhe National Nature Reserve are described: Draconarius gengma Kong, Yang & Zhang, sp. nov., D. meniscatus Kong, Yang & Zhang, sp. nov., D. nangunhe Kong, Yang & Zhang, sp. nov., D. nantianmen Kong, Yang & Zhang, sp. nov., Sinocoelotes subwa Kong, Yang & Zhang, sp. nov., and S. wa Kong, Yang & Zhang, sp. nov. Photos of bodies and genitalia of all species are also provided.